USE OF ULTRASOUND EXAMINATION AS A METHOD OF DIAGNOSTICS OF SMALL ANIMALS’ REPRODUCTIVE SYSTEM PATHOLOGIES - Kyrychko, B. P.; Zvenihorodska, T. V.; Kyrychko, O. B. (Scientific Progress & Innovations, 2021)
Due to an increase in the number of the reproductive system diseases of small animals, such as endometritis, polycystic ovaries, the need arises to use modern, highly effective methods of diagnosing these pathologies. 47 dogs and 103 cats aged from 1 year to 18 years old, having the following clinical signs: discharges from the external genital organs, an increase in the volume of the abdominal cavity, its pain, polyuria and polydipsia, were taken for studies in the scientific, training and production clinic of Poltava State Agrarian University The research was also carried out on the animals’ problems concerning fertilization, long anestrus, and dysfunction of the sexual cycle. When examining the uterus and ovaries, animals were placed in spinal and right and left side positions to create three acoustic windows: along a white abdominal line from the pubic bone to the umbilical area; from the caudal apex of the right kidney to the iliac zone; from the caudal apex of the left kidney to the iliac area. The ultrasonic gel was applied to the examined areas and a linear sensor was installed immediately in front of the rotating paging, orienting the scan plan in turn, strongly and segmental. At first, the urinary bladder was visualized, then the body of the uterus. Ultrasound examination was conducted in B-mode. It has been found that the average age of cats with pathologies of the reproductive system was 3.2±0.5 years, the average age of dogs – 6.2±1.1 years. It has been established that the most common pathologies of the reproductive system in small animals are endometritis, piometra and glandular-cystic hyperplasia of cell endometrium. The signs of endometritis on the ultrasound map are thickening, unevenness and hyperechogenic walls of the uterus body and horns, possible presence of anechoic content. Piometra is the second among the reproductive system pathologies of the examined dogs (21.3 %), and the third among the investigated cats (8.7 %). The smallest share among the reproductive system pathologies is taken by the ovarian diseases. The dogs’ ovarian pathologies made 6.4 %, and cats’ – 7.8 %.